Green- to far-red-emitting fluorogenic tetrazine probes: synthetic access and no-wash protein imaging inside living cells - Wieczorek, Achim; Werther, Philipp; Euchner, Jonas; Wombacher, Richard (Chemical science, 2017)
Fluorogenic probes for bioorthogonal labeling chemistry are highly beneficial to reduce background signal in fluorescence microscopy imaging., Fluorogenic probes for bioorthogonal labeling chemistry are highly beneficial to reduce background signal in fluorescence microscopy imaging. 1,2,4,5-Tetrazines are known substrates for the bioorthogonal inverse electron demand Diels-Alder reaction (DAinv) and tetrazine substituted fluorophores can exhibit fluorogenic properties. Herein, we report the synthesis of a palette of novel fluorogenic tetrazine dyes derived from widely-used fluorophores that cover the entire emission range from green to far-red. We demonstrate the power of the new fluorogenic probes in fixed and live cell labeling experiments and present the first example of intracellular live cell protein imaging using tetrazine-based probes under no-wash conditions.
Accepted 19th October 2016
Gesehen am 18.10.2018